PENGEMBANGAN INSTRUMEN TES UNTUK MENGUKUR HIGHER ORDER THINKING SKILLS (HOTS) PESERTA DIDIK PADA MATERI SUHU DAN KALOR SMA - AyuWandira, Dayang; Hamdani, Hamdani; Firdaus, Firdaus (Institut Pendidikan Tapanuli Selatan, 2025)
This research aims to produce a two-tier multiple choice test instrument that is suitable for measuring students' HOTS on temperature and heat material. The research method used is research and development with a 4D model. Research data was taken from 200 class XI students at SMA Negeri 10 Pontianak and SMA Negeri 3 Pontianak. Analysis of test item characteristics was carried out with the Rasch Model using Winstep and SPSS. The expert validation results are very high with a value of 0.97, the average readability score is 6.86, indicating that the question text is easy for high school students to understand, and the construct validation results show that the test can measure 76.96% of the constructs to be measured. The Rasch model shows unidimensionality. 26.9% (fair), person reliability 0.73 (fair), item reliability 0.90 (good), there are 13 items that fit the Rasch model, and the test instrument is divided into 2 very easy questions, 7 easy questions, 3 questions very difficult, and 3 questions are difficult. Then 1 question item has poor discriminating power, 3 questions have sufficient power, and 11 questions have good discrimination. Based on these results, there are 13 questions that are suitable to be used to measure students' high-level thinking abilities on temperature and heat material.